2023
DOI: 10.1002/adma.202306246
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Lipid Nanoparticles for Renal Cell Carcinoma

Xiongmin Mao,
Guanyi Wang,
Zijian Wang
et al.

Abstract: Renal cell carcinoma (RCC) is a common urological malignancy and represents a leading threat to healthcare. Recent years have seen a series of progresses in the early diagnosis and management of RCC. Theranostic lipid nanoparticles (LNPs) are increasingly one of the focuses in this field, because of their suitability for tumor targeting and multimodal therapy. LNPs can be precisely fabricated with desirable chemical compositions and biomedical properties, which closely match the physiological characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 240 publications
0
0
0
Order By: Relevance
“…The ongoing progress in nanotechnology has led to the identification of novel applications for various types of nanomaterials such as natural, synthetic, inorganic, and lipid nanomaterials [ [27] , [28] , [29] ]. Nanomaterials exhibit superior drug delivery and targeting capabilities compared to conventional materials, as well as enhanced functionalization of drug carrier surfaces.…”
Section: Materials Used For Early Diagnosis Of Rccmentioning
confidence: 99%
“…The ongoing progress in nanotechnology has led to the identification of novel applications for various types of nanomaterials such as natural, synthetic, inorganic, and lipid nanomaterials [ [27] , [28] , [29] ]. Nanomaterials exhibit superior drug delivery and targeting capabilities compared to conventional materials, as well as enhanced functionalization of drug carrier surfaces.…”
Section: Materials Used For Early Diagnosis Of Rccmentioning
confidence: 99%
“…Lipid nanoparticles (LNPs) are excellent carriers for targeted drug delivery due to their good biocompatibility and high loading capacity. , In addition to being vaccine carriers, , LNPs have other applications, such as genomic drugs , and tumor immunotherapy. , Although an increasing amount of basic research on LNPs has been reported, , clinical applications are still limited by their effectiveness and safety. Once LNPs are introduced into the body, they may be damaged by several adverse factors, leading to LNP rupture.…”
Section: Introductionmentioning
confidence: 99%